Norm Effects on Gender in Social Marketing Advertising Campaigns Promoting Savings Behavior. Issue 1 (2nd January 2017) - Yoon, Hye Jin; La Ferle, Carrie; Edwards, Steven M.
ABSTRACT: Although using social norms has been effective in changing behaviors in various areas, including pro-environmental behavior, pro-health behavior, and financial decisions, possible gender differences in response to norm effects have seldom been tested. With an understanding of the orientation differences of genders, this research proposes that men and women will respond differently to social norm information varying in the proximity of reference groups and information valence, which are two core elements of social norm information. Two experiments are conducted to test for this proposition using social marketing advertising campaigns promoting pro-savings behavior. The findings provide theoretical implications for differential norm effects on gender and practical implications for social marketing campaigns that incorporate social norm information.